Estimating the Company Value of PT Adaro Energy TBK: A coal Mining Company - Mubarak, Mulham Anugrah; Surya, Budhi Arta (Journal of Business and Management, 2012)
PT Adaro Energy Tbk is one of the major coal mining companies in Indonesia. It is currently Indonesia’s second largest thermal coal producer. PT Adaro Energy Tbk itself had been operated since 1992 in South Borneo but then it was still a small company that engaged in coal mining sector. This company releases its open public and offering period on July 8th until 10th 2008 and listed its shares in Jakarta Stock Exchange on July 16th 2008 with PT Danatama as the Underwriter. When established on July 28th 2004. this company has basic capital of IDR 8.000.000.000.00. From year to year since it was established. PT Adaro Energy Tbk has an excellent performance. In 2010. the production reaches 42.2 million tons and the sales reaches 2.7 million dollars. An excellent performance company surely has to maintain and always improve its performance. Therefore. a valuation is needed to measure the value of the company and knowing how to enhance the value. Author used three kind of approaches to estimate the value of the company. which are asset-based approach. income approach and market approach. Author will also determine the share value based on the value that had been determine using each approaches that have been told before. Purpose: The research is made to estimate the value of PT Adaro Energy Tbk and by that. knowing what should be done by the company depend on what shouldbe done by the company depend on what is the value of the company. Authow will use some valuation methods and techniques accordance with the company conditions and structures.Design/methodology/approach: The methods that used in this research paper were asset-based approach. income approach (Discounted Cash Flow). and market approach. Author will use the consolidated financial statements of PT Adaro Energy Tbk from year 2006-2011.Findings: Using those three kinds of approaches. author will find the estimated value. Then. after find the estimated value of the company. the stock value will be found by using the equation which will be used in analysis. The reasearch shows that the value of PT Adaro Energy Tbk is ranged between IDR 43.361.609.266.373.00 to IDR 354.399.618.736.223.00 and the stock value with the current share price IDR 1.460.00 (31 July 2012) is ranged between IDR 972.91 to IDR 10.378.65. This shows that PT Adaro Energy Tbk has a big potency to enhance its value and PT Adaro Energy Tbk is still a good choice to investors.Research limitations/implications: This research is focuses on determining the estimated value and share value of PT Adaro Energy Tbk. In one of the approaches. author will use the P/E ratio from the public coal mining industries which listed in IDX.Originality/value: This research paper contains about measuring the estimated value and share value of PT Adaro Energy Tbk using three approaches. This valuation is important in order if PT Adaro Energy Tbk wants to sell its assets or wants to do merger and acqusition. It also important for a company to enhance its company value.Keywords: Valuation;asset-based approach;income approach;discounted cash flow; market approachCategory: Finance